'Muddling Through' in the Biological and Toxin Weapons Convention. Issue 3 (May 2018) - Revill, James
Abstract This article looks at power in the origins and evolution of the Biological and Toxin Weapons Convention (BWC) with a focus on five episodes in the evolution of biological disarmament. The first is the origins of what some have termed a taboo surrounding poison weapons. The second is the role of different forms of power in the negotiation of the 1925 Geneva Protocol; and, third, is the decision by President Nixon to renounce biological weapons in 1969. The fourth episode is the collapse of negotiations on a BWC Protocol in 2001, and the fifth is the subsequent work of states parties during the intersessional processes. The chapter illustrates the complex and the polymorphous character of power in the biological disarmament regime with compulsory, institutional, productive and to a lesser extent structural forms of power playing a role. The paper concludes by exploring the literature on public administration, particularly Lindblom's notion of 'incrementalism' to outline how diffuse institutional power effectively means the BWC has been forced to 'muddle through' in an incremental manner.